EVALUASI KINERJA PENGASUH DALAM PEMBENTUKAN KEPRIBADIAN PRAJA DI INSTITUT PEMERINTAHAN DALAM NEGERI KAMPUS JATINANGOR (STUDI KASUS PENGASUH WISMA SATUAN MUDA WANITA PRAJA) - Situmorang, Verycia Angelina (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2019)
Institut Pemerintahan Dalam Negeri (IPDN) is one of educational institution under the authority of ministry of Internal Affairs which aims to prepare the cadets of Internal Goverment, To produce a cade of goverment who has a good personality, attitudes adn behaviour of civilness it's very influenced by the ability of the caregiver as forming the personality of the civil. The background of this research is because there are many infraction done by Young female Caregiver Pensions Unit Praja, it show that lack performances from the caregiver. The purpose of this study is know and analyze the performance evaluation of caregivers performance to build and forming personality of praja in Institut Pemerintahan Dalam Negeri Jatinangor and what factors are affecting the performance of the caregiver. This research uses the mixedmethod research and the data collection techniqu used is interview, observation, documentation and assisted with quetionaire technique/ The result shows that performance of caregivers to forming or build teh personality of praja is good but it is not yet maximal. It because the ability of caregivers is not adequate. And the recruitment of caregivers in Institut Pemerintahan Dalam Negeri do not run in accordance with the rules. Therefore, in this thesis researcher give some advice need to get a recruitment of caregivers in accordance with the rules, need to give caregivers some training to incrase their ability to farming personality of praja. And then need to have a good evaluation tools to know how far performance of the caregivers.